Malaysia’s Neocolonial Struggle: Unraveling the Complexities of Postcolonial Dynamics - J. Roknifard (Международная аналитика)
The article dissects the case of Malaysia in the context of postcolonial studies. After an introduction to the aspects of postcolonial studies that are instrumental in analyzing the case, the article begins by exploring the postcolonial landscape of Malaysia, including the existing discourses, values, and the public sentiments they embody. It then highlights signiﬁcant milestones in the country’s foreign policy and provides a comparative perspective on diﬀerent periods. Finally, it assesses the most recent developments related to the geopolitical power struggle between China and the US in Southeast Asia. The article’s main thesis argues that Malaysia has not fully undergone the process of decolonization. Initially, the ruling political elite preserved some colonial instruments to maintain their own dominance, and later, Malaysia became entangled in the rivalry between the US and China, with both establishing neocolonial dominance over the country in diﬀerent ways. Malaysia’s history since independence has not led to the formation of a cohesive nation, which has exposed it to foreign inﬂuence that exploits gaps in national consciousness and modes of governance.